Marketing Strategy of Aceh Dodol Cake Products, in Gampong (Village) Matang Kruet in Increasing Customer Satisfaction in Lhok Nibong Town, Sub-District Pante Bidari District East Aceh - Hartika, Feni Putri; Iryani, Lisa; Ameliany, Nanda; Sufi, Sufi; Nursanjaya, Nursanjaya (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
The purpose of this observation is to find out the marketing strategy carried out in the Aceh dodol cake production business in increasing customer satisfaction at Matungan Kruet. By using the three marketing strategy indicators, product, price and promotion. This research uses a qualitative descriptive approach with data collection including observation. , interviews and documentation. The informants in this research consisted of 1 key informant and 4 supporting informants. The results of this research indicate that the role of the product in supporting increased customer satisfaction in the production of Aceh dodol cake is by maintaining the quality of the product and the ingredients used in accordance with customer wishes. The role of price in supporting increased sales in the Aceh dodol cake business by setting prices in accordance with the quality of the product and the target market. The role of promotion in increasing sales in the Aceh dodol cake business is by utilizing social media as a form of promotion such as Facebook and WhatsApp. So the three indicators such as product, price and promotion in marketing strategies can increase sales and increase customer satisfaction.